-8(1-7n)+7(n+3)=

Simple and best practice solution for -8(1-7n)+7(n+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(1-7n)+7(n+3)= equation:


Simplifying
-8(1 + -7n) + 7(n + 3) = 0
(1 * -8 + -7n * -8) + 7(n + 3) = 0
(-8 + 56n) + 7(n + 3) = 0

Reorder the terms:
-8 + 56n + 7(3 + n) = 0
-8 + 56n + (3 * 7 + n * 7) = 0
-8 + 56n + (21 + 7n) = 0

Reorder the terms:
-8 + 21 + 56n + 7n = 0

Combine like terms: -8 + 21 = 13
13 + 56n + 7n = 0

Combine like terms: 56n + 7n = 63n
13 + 63n = 0

Solving
13 + 63n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 63n = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 63n = 0 + -13
63n = 0 + -13

Combine like terms: 0 + -13 = -13
63n = -13

Divide each side by '63'.
n = -0.2063492063

Simplifying
n = -0.2063492063

See similar equations:

| 5n-3n+7+2n= | | 24a+72b-40c= | | 13*0*p=0 | | 6j-4j+12=6j-3j+30 | | 42-48v=-54 | | 9=8-x/4 | | 4(2a)-a= | | 4w-5=12w-4 | | (4x^2-1)(6x^2-9)= | | 5(d+5)+2d=-13-8d | | 1/3x-8=4/9x | | 20=a/9 | | 26=13/v | | -7(3a-2)+4(5a+5)= | | 10=6+(1+3m)-2(2+10m) | | X-y=110 | | 7x-3x(x+1)= | | 6+2[3j-2]=4[1+j] | | 1/y-1/2=4 | | 6(z/2-5)=36 | | q=10000-125p | | 12x^2-121/12=0 | | 12=m/5 | | X+y=280 | | 5.5=-1.5+x | | 2.3+n+1.4=0 | | x-86=135 | | -2(-5v+5)=5[2v+3(v+1)] | | Y=x^2-10x+45 | | 3(4x-3)+8x=68 | | 14xy-4xy=o | | -7=-17+x |

Equations solver categories